2019
DOI: 10.1080/07373937.2019.1670672
|View full text |Cite
|
Sign up to set email alerts
|

Electrically enhanced drying of white champignons

Abstract: Electrohydrodynamic (EHD) drying is a novel non-thermal dewatering technology using electric discharge in air to enhance dehydration of heatsensitive biomaterials. Low energy consumption and high product quality make it attractive for industry. In this study, the mushrooms slices have been dried under sole EHD with 12, 14, and 16 kV DC, and EHD in combination with air cross-flow at 1 m s-1 and different relative humidity (RH) from 30 to 70 %. It was found that drying kinetics was exponential over initial moist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 27 publications
6
14
0
Order By: Relevance
“…The effective moisture diffusivity increased considerably with an increase in air velocity ( Figure 7 ). This concurs with the observations on the EHD drying of white champignons with forced air convection [ 12 ]. The effect of temperature was also significant.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The effective moisture diffusivity increased considerably with an increase in air velocity ( Figure 7 ). This concurs with the observations on the EHD drying of white champignons with forced air convection [ 12 ]. The effect of temperature was also significant.…”
Section: Resultssupporting
confidence: 92%
“…Bai et al [ 6 ] reported that low RH is beneficial for EHD drying of fish. Similar observations were made by Martynenko et al [ 12 ] for EHD drying of mushroom slices. In a literature review by Zhang et al [ 13 ] on the effect of RH on hot air drying of fruits and vegetables, it was reported that high RH could facilitate heat transfer and increase the drying rate in the constant rate period of drying.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…increased increased from 1.37 Â 10 À8 to 2.86 Â 10 À8 m 2 /s as voltage increased from 0 to 30 kV in EHD drying of carrot slices. Also, the same results were announced by previous literature for the EHD drying of white champignons (Martynenko, Bashkir, & Kudra, 2019) and Chinese Wolfberry (Ding & Yang, 2017). When the distance between needles was 6 cm, the D eff of the apple slices was generally higher.…”
Section: Drying Process and Drying Ratesupporting
confidence: 87%
“…Here, decreasing air humidity from 70 to 30% significantly increased drying rate (drying constant increased more than threefold from 0.12-0.13 to 0.45-05 kg water/kg/h). The results from complete experiments are given in the recent paper by Martynenko et al [18].…”
Section: Dehumidifying Of Drying Airmentioning
confidence: 99%